Humans as Noble Creatures, Caliphs, and Educators: Studies in Islam - Wan Muhammad Fariq; Suci Amanda; Dea Anggini (Kasyafa: Jurnal Pendidikan Agama Islam, 2024)
The research titled " Human as a Noble Being, Caliph, and Educator: A Study in Islam " aims to explore and understand Islamic views on the essence and role of humans within spiritual and social contexts. This study utilizes a literature review approach, gathering data from the Qur'an, Hadith, relevant books, and exegeses. The data is analyzed using content analysis techniques to identify and elaborate on key concepts related to Islamic perspectives on humanity. The research examines three main aspects: 1) the concept of humans as noble creatures, reflecting the value and honor of humans according to Islamic teachings; 2) the role of humans as stewards on Earth, responsible for managing and maintaining the environment and society in line with Islamic principles; and 3) the capability of humans to be educated and to educate, reflecting the potential for learning and self-development within the framework of Islamic teachings.